Doomed to fail? A qualitative exploration of teachers’ perspectives on refugee students’ access to education and educational experiences in Greece - Theoni Stathopoulou; Eirini Adamopoulou; Lina Zirganou-Kazolea; Natalia Spyropoulou; Korina Hatzinikolaou; Jennifer Cavounidis (Genus)
Abstract Equitable educational opportunities, in terms of access to quality education and resources in the host countries, are crucial to the individual personal development of refugee minors, promoting psychosocial well-being and resilience despite significant adversity. Meanwhile, participation in the education system of the host country facilitates social integration. This qualitative study explored teachers’ views on factors influencing access to education and educational experiences of refugee students 12- to 18‐year old in Greece. Two focus groups were used to examine teachers’ views on the positive and negative factors affecting refugee minors’ access to education and educational experiences. Thematic analysis resulted in three main themes: (a) institutional barriers, (b) the pivotal role of an inclusive school culture, and (c) the reception class as a transitional space. Findings indicate that meaningful inclusion in terms of access to education, appropriate teaching, and a supportive learning environment remains elusive in Greece for students with refugee backgrounds, given that their educational experiences are usually limited to participation in reception classes designed almost exclusively to teach the host country’s language (Greek). Although, reception classes can indeed serve as an effective transitional space for refugee minors, facilitating school achievement, well-being, and social integration, they must be complemented by a long-term and broadened education policy that actively promotes refugee minors’ social inclusion in regular school classes alongside their native peers.